PAPR Reduction in FBMC-OQAM Systems Using Trellis-based D-SLM with ABC Algorithm - Jirajaracheep, Panya; Mata, Tanairat; Boonsrimuang, Pisit (My University, 2020)
For the next age of mobile and wireless communications systems. Filter bank multicarrier conjunction with offset quadrature amplitude modulation (FBMC-OQAM) is the non-orthogonal multicarrier modulation techniques, which is mention as an essential and prominent player. It has several advantages, such as higher spectral efficiency, as compared to the traditional methods. Nevertheless, FBMC-OQAM still has a critical weakness similar to OFDM system, which is a high peak-to-average power ratio (PAPR) at the transmitter. There are several varieties of the technique presented to defeat the severe PAPR issue. The Trellis-based D-SLM technique is presented to employ and achieve a significantly improve PAPR curtailment performance. However, The Trellis-based method still has a limitation of its high computational complexity. This study presents the Trellis-based D-SLM scheme with artificial bee colony (ABC) phase optimization, which achieves lower computational complexity. The results of PAPR performance evaluation through computer simulation, the proposed technique can deliver a performance of PAPR reduction similar to the conventional Trellis-based D-SLM technique, but the proposed technique requires around 10% computation complexity of the conventional technique.
Keywords: ABC phase optimization; D-SLM; FBMC-OQAM; PAPR; Trellis-based D-SLM